Phenomena of Absorption of Soft and Hard Components of Space Rays in the Atmosphere in Yerevan Conditions - Taroyan, A. S.; Kokanyan, E. P.; Taroyan, Yu. A.; Mkhitaryan, N. N.
The article examines the angular distribution of cosmic ray intensity and identifies the triads using two different empirical formulas for their distribution. The total absorption coefficient of soft and hard components was measured.
Keywords: Physics